Revisiting the different responses of the following Indian summer monsoon rainfall to the diversity of El Niño events - Zhang, Xiya; Xu, Kang; Wang, Weiqiang; He, Zhuoqi (Frontiers in Earth Science, 2022)
There is evidence that the interannual relationship between El Niño events and the following Indian summer monsoon rainfall (ISMR) has weakened with the more frequent occurrence of central Pacific (CP) El Niño events. We revisited the following ISMR responses to the two different types of El Niño events using observations and reanalysis datasets. Our results show that the ISMR anomalies associated with eastern Pacific (EP) and CP El Niño events are different, with decreased (increased) rainfall in early summer (June–July) following EP (CP) El Niño events. This is primarily attributed to the different responses to anomalous warming of the sea surface temperature (SST) in the northern Indian Ocean (NIO), which is characterized by double peaks in the warming SST during EP El Niño events, but only one peak during CP El Niño events. For EP El Niño events, the second SST warming peak in early summer contributes to the lower level antisymmetric wind pattern over the tropical Indian Ocean (TIO), which delays the onset of the Indian summer monsoon (ISM) and decreases the supply of moisture to India, implying a decrease in the ISMR. By contrast, for CP El Niño events, the cooling SST over the western TIO directly induces a significantly positive meridional SST gradient and drives the lower level southwesterly wind anomalies, resulting in an eastward shift in the decreased antisymmetric winds over TIO and the early onset of ISM. These circulation features are associated with anomalous upper-level divergence over TIO and sinking over India, jointly leading to the excess ISMR in early summer. These results suggest that, in addition to the key role of the warming of the NIO SST, cooling of the SST over the western TIO during CP El Niño events should be considered carefully in understanding the El Niño–ISMR relationship.